PENGARUH PENGETAHUAN ORANG TUA TENTANG ORTODONSI PREVENTIF DENGAN PERILAKU PENCEGAHAN MALOKLUSI PADA GIGI ANAK - M Yaqiudin Aditya; Moh. Baehaqi; Rahmawati Sri Praptiningsih (ODONTO : Dental Journal, 2015)
Background: Malocclusion is abnormal occlusion which signed the unsimetric position of its teeth that caused by genetic factor, unappropiate development, bad habit and malnutrition. The children who got malocclusion problem doesn,t need any attention because children usually still lack of responsbility to take care the dental problem. That,s why the role of parents is very needed. Parents knowledge about preventive ortodensi can make easier to prevent children malocclusion. Purpose: The purpose of this research is to know the influence of parents knowledge about preventive ortodensi to prevent children malocclusion. Method: This research using analitic observational with survey cross sectional method. Data comes from kuisioner. The parents knowledge means everything about the prevention of malocclusion, meanwhile preventive action is the action to handle malocclusion itself. wIlcoxon experiment is used for analitical tool with p < 0.05. Result: The result shown that the parents knowledge about ortodensi will appear better to parents who got the bachelor or diploma degree (65.9%). And preventive action for malocclusion also shown better from parents with bachelor or diploma degree also (71.05%). Conclusion: The conclusion is the influence of parents knowledge about malocclusion prevention in children teethwith level of (p=0.001) with confident level 90%.